Effects of Risk, Profitability, Firm Reputation on Intellectual Capital Disclosures: Evidence from Indonesia - Saarce Elsye Hatane; Ang Kezia Christabel; Daniella Britney (Universitas Pendidikan Ganesha, 2021)
This research aims to discover the factors that could influence Intellectual Capital Disclosure (ICD) on tourism companies in Indonesia. The research samples were 29 Indonesian tourism companies listed on the Indonesia Stock Exchange (IDX) from 2015 until 2019. This research used the panel data regression model with corporate risk, profitability, firm reputation, firm size, financial leverage, and ICD alongside its components as the tested variables. The main finding of this research was that firm risk and profitability positively influence ICD. In contrast, firm reputation negatively impacts ICD. The results also revealed that HCD was the most disclosed component. Therefore, the utilization and disclosure of IC could increase firm value and firm financial performance. Moreover, ICD could help investors in their consideration of investment decisions.